Effect of Supply Chain Disruption in Dental Practice During Covid-19 Pandemic: An Indian Perspective - Vibha Joshi; Nitin Joshi; Komal Bajaj; Pankaj Bharadwaj; Kuldeep Singh (National Journal of Community Medicine, 2022)
Disruption during Covid-19 pandemic highlighted the need for healthcare supply chain management in order to achieve effective delivery of health services. Though considerable efforts have been undertaken on managing the healthcare supply chain disruptions in India but there is a paucity of literature that documented the effect of supply chain disruptions in dental practices during a covid-19 pandemic. During a pandemic, the disruptions in production and distribution of dental products were seen in India. Indian dental market is largely dependent on imports and there is a scarcity of local production units. The main dental companies reported a significant decline in production during the first wave of Covid-19. The increase in demand for dental supplies was seen with a shutdown, shortage of labor, and scarcity of raw materials. Disruption rippled through the supply chain and this was caused by a large distortion in demand. This phenomenon led to the bullwhip effect. This bullwhip effect crisis led to increased costs in dental practices. Covid19 has shown a significant lack of resilience in the Indian dental healthcare supply chain. This study identified a few loopholes in the dental supply chain and suggested a way forward for managing the supply chain disruptions. It seems that there is a need for more comprehensive research on dental supply chain resilience from an Indian perspective to prevent disruptions, particularly in emergent situations.